Effectiveness of a Web-Based SUpport PRogram (SUPR) for Hearing Aid Users Aged 50+: Two-Arm, Cluster Randomized Controlled Trial - Meijerink, Janine FJ; Pronk, Marieke; Lissenberg-Witte, Birgit I; Jansen, Vera; Kramer, Sophia E (JMIR Publications, 2020)
BackgroundHearing aid (HA) use is known to improve health outcomes for people with hearing loss. Despite that, HA use is suboptimal, and communication issues and hearing-related activity limitations and participation restrictions often remain. Web-based self-management communication programs may support people with hearing loss to effectively self-manage the impact of hearing loss in their daily lives. ObjectiveThe goal of the research is to examine the short- and long-term effects of a web-based self-management SUpport PRogram (SUPR) on communication strategy use (primary outcome) and a range of secondary outcomes for HA users aged 50 years and older. MethodsClients of 36 HA dispensing practices were randomized to SUPR (SUPR recipients; n=180 HA users) and 34 to care as usual (controls; n=163 HA users). SUPR recipients received a practical support booklet and online materials delivered via email over the course of their 6-month HA rehabilitation trajectory. They were encouraged to appoint a communication partner and were offered optional email contact with the HA dispensing practice. The online materials included 3 instruction videos on HA handling, 5 videos on communication strategies, and 3 testimonial videos. Care as usual included a HA fitting rehabilitation trajectory only. Measurements were carried out at baseline, immediately postintervention, 6 months postintervention, and 12 months postintervention. The primary outcome measure was self-reported use of communication strategies (3 subscales of the Communication Profile for the Hearing Impaired [CPHI]). Secondary outcome measures included self-reported personal adjustment to hearing loss (CPHI); use, satisfaction and benefit of HAs and SUPR (use questionnaire; International Outcome Inventory for Hearing Aids [IOI-HA], Alternative Interventions [IOI-AI]); recommendation of HA dispensing services; self-efficacy for HA handling (Measure of Audiologic Rehabilitation Self-Efficacy for Hearing Aids [MARS-HA]); readiness to act on hearing loss (University of Rhode Island Change Assessment adapted for hearing loss [URICA-HL]); and hearing disability (Amsterdam Inventory for Auditory Disability and Handicap [AIADH]). ResultsLinear mixed model analyses (intention to treat) showed no significant differences between the SUPR and control group in the course of communication strategy use (CPHI). Immediately postintervention, SUPR recipients showed significantly higher self-efficacy for advanced HA handling than the controls, which was sustained at 12 months (MARS-HA; mean difference immediately postintervention: 5.3, 95% CI 0.3 to 10.4; P=.04). Also, SUPR recipients showed significantly greater HA satisfaction than controls immediately postintervention (IOI-HA; 0.3, 95% CI 0.09 to 0.5; P=.006), which was sustained at 12 months, and significantly greater HA use than the controls immediately postintervention (IOI-HA; 0.3, 95% CI 0.02 to 0.5; P=.03), which was not sustained at 12 months. ConclusionsThis study provides ground to recommend adding SUPR to standard HA dispensing care, as long-term, modest improvements in HA outcomes were observed. Further research is needed to evaluate what adjustments to SUPR are needed to establish long-term effectiveness on outcomes in the psychosocial domain. Trial RegistrationISRCTN77340339; http://www.isrctn.com/ISRCTN77340339 International Registered Report Identifier (IRRID)RR2-10.1136/bmjopen-2016-015012